2016
DOI: 10.1177/1758998316657844
|View full text |Cite
|
Sign up to set email alerts
|

Introducing purposeful activity kits in a hand rehabilitation practice: Effects on clinical practice patterns and job satisfaction among occupational therapy practitioners

Abstract: Introduction: Facilitating function through occupation and purposeful activity is the basic tenet of occupational therapy. However, the majority of research in hand rehabilitation clinics continues to focus on biomechanical interventions. The purpose of this research was to study practice patterns and personal opinions of occupational therapy practitioners before and after providing purposeful activity kits to an outpatient occupational therapy hand clinic. Methods: Mixed-method design to evaluate an 8-week in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…However, there is often a disconnection between the theoretical underpinnings of occupational therapy (OT) and typical hand therapy clinical practice. 6 Hand therapy is traditionally based on the biomechanical model, 7 which focuses on isolated aspects of human functioning, such as body functions and structures alone. 8 Research suggests that a more comprehensive and occupation-based approach to hand therapy will produce better outcomes when compared to this isolated biomechanical approach.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is often a disconnection between the theoretical underpinnings of occupational therapy (OT) and typical hand therapy clinical practice. 6 Hand therapy is traditionally based on the biomechanical model, 7 which focuses on isolated aspects of human functioning, such as body functions and structures alone. 8 Research suggests that a more comprehensive and occupation-based approach to hand therapy will produce better outcomes when compared to this isolated biomechanical approach.…”
Section: Introductionmentioning
confidence: 99%
“…21 Research identified four primary reasons hand therapists do not deliver occupation-based care: insufficient time, lack of equipment, productivity and reimbursement demands, and reliance on protocols and treatment prescriptions. 6,10,19,21 Hand therapists affirm the value of using occupation-based assessments and interventions and would like to incorporate them more systematically into their practice, but they do not have the tools to do so. 19,21 Bridging the gap to provide skilled, holistic, client-centered care is a challenge that many practicing therapists face.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations